One Small Step for the Gram Stain, One Giant Leap for Clinical Microbiology - Thomson, Richard B. (J Clin Microbiol, 2016)
The Gram stain is one of the most commonly performed tests in the clinical microbiology laboratory, yet it is poorly controlled and lacks standardization. It was once the best rapid test in microbiology, but it is no longer trusted by many clinicians. The publication by Samuel et al. (J. Clin. Microbiol. 54:1442–1447, 2016, http://dx.doi.org/10.1128/JCM.03066-15) is a start for those who want to evaluate and improve Gram stain performance. In an age of emerging rapid molecular results, is the Gram stain still relevant? How should clinical microbiologists respond to the call to reduce Gram stain error rates?